Reframing hunting, gathering, tool-making and art, as expressions of evolution of consciousness as depicted in Jean Gebser"s "the ever-present origin" - Ilongo, Fritz N. (HTS teologiese studies, 2017)
This article explores the evolution of consciousness as directly correlated to hunting, gathering, tool-making and art. The methodology is qualitative theoretical analyses, articulated around Jean Gebser’s seminal work, The Ever-Present Origin. Hunting and gathering are expressions of a magical, unitary, ‘self-dissolving’ consciousness. Tool-making on the other hand is depicted as evolving from a mythical consciousness of duality, polarity, symbolism and a state of being qualified by ‘crystallisation of the I’. Lastly, art is a function of a consciousness of ‘self-transcendence’, ‘I and I’, idealisation and a transpersonal state of being. The article concludes by positing that hunting, gathering, tool-making and art can be reframed as ‘forms of the movement of consciousness’.